2020
DOI: 10.3390/vaccines8020148
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Workers’ Knowledge, Attitudes, and Practices about Vaccinations: A Cross-Sectional Study in Italy

Abstract: The cross-sectional study assessed the knowledge, attitudes, and practices regarding the recommended vaccinations and factors affecting such outcomes among a sample of healthcare workers (HCWs) in public hospitals in Italy. Only 14.1% knew all the recommended vaccinations for HCWs. Physicians and those who had received information about vaccinations from scientific journals, educational activities, or professional associations were more likely to have this knowledge, while those aged 36–45 were more likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
50
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 28 publications
11
50
4
1
Order By: Relevance
“…According to our experience, referring to PHPs, 57.1% of the study sample was aware of all recommended vaccinations for HCWs (with a higher degree of knowledge in northern regions than in southern regions), unlike some other Italian studies that included all HCWs and reported lower values [23,24].…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…According to our experience, referring to PHPs, 57.1% of the study sample was aware of all recommended vaccinations for HCWs (with a higher degree of knowledge in northern regions than in southern regions), unlike some other Italian studies that included all HCWs and reported lower values [23,24].…”
Section: Discussionmentioning
confidence: 68%
“…Several surveys have been carried out worldwide on the knowledge, attitudes, and practices of HCWs in relation to vaccinations [23,38,39], but very few have specifically studied PHPs [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthcare professionals, who handle the patients and their clinical specimens, are at increased risk of acquiring HBV infection. As recommended by the WHO's Knowledge, Attitude, and Practice study, a good knowledge of the HBV virus, attitude for control or prevention, and vaccination practices are the mainstay to prevent the infection in healthcare settings [5][6][7].…”
Section: Introductionmentioning
confidence: 99%